An Empirical Study of the Capital Structure Theories on Philippine Listed Firms - Meneses, John Philip B.; Palo, Mary Lourdes C. (Philippine Management Review; Vol 30 (2023), 2023)
This study aims to determine whether the Trade-Off Theory and the Pecking Order Theory are able to explain the financing behavior of Philippine listed firms using data from 2010 to 2019. Analysis on the relationship of firm-specific variables against leverage as well as individual and joint testing of the TO and PO models were performed using panel data regression. The results have shown that while no model is dominant over the other, both capital structure theories are evident in the financing behavior of Philippine listed firms. Growth opportunity and profitability exhibit a positive and negative relationship with leverage, respectively, supporting the Pecking Order Theory. While firm size has shown a positive relationship with leverage, supporting the Trade-Off Theory. Individual and joint testing of the capital structure models were also able to provide significant results in support of both models.